Food allergy testing in infantile eczema: A clinical approach and algorithm. (12th June 2012) - Newland, Kate; Warren, Lachlan; Gold, Michael
ABSTRACT: The complex relationship between food allergy and infantile eczema has prompted divergent approaches to investigating potential food triggers in eczematous patients. It is well recognised that a significant proportion of infants with eczema have immunoglobulin E‐mediated food allergy, reported to range between 20–80%. Determining whether certain foods trigger an eczematous flare in individual infants with eczema is difficult. For all infants with eczema, good skin care is the mainstay of treatment but identifying and avoiding triggers (both allergic and non‐allergic) is important in some infants. Given this, we have a developed an algorithm that can be used by dermatologists in the investigation and management of food allergies in infantile eczema. Issues such as patient selection, investigation and elimination diets are addressed, with reference to relevant evidence in the literature. Our aim is to provide dermatologists with a framework to manage food allergies in infantile eczema, allowing the problem to be addressed with confidence.